Prediction on Target of Underprivileged Scholarships Using Fuzzy Logic Method - Afifah Rodhiyatun Nisa; Daffa Adrian Ahmadi Tondang; Fauzan Perdana Ilham; Ghani Trie Aqeela Ramadhani; Muhammad Danang Mukti; Fiqri Nurfadillah; Nanda Octavia (Journal of Applied Science, Technology & Humanities | JASTH, 2024)
Education is key to the country's development, but in Indonesia, financial constraints for students often occur. In Java, population density and poverty are high, making it difficult for students. The government strives with scholarship programs, such as Bidikmisi/KIP Perguruan (Bidikmisi/KIP Lecture), Baznas Institute, KJMU, West Java Leadership Scholarship. However, scholarship disbursements often face misappropriation and discrepancies. Therefore, a Fuzzy Logic calculation is performed. This research uses the Mamdani Fuzzy Logic method to overcome this. This method is accurate and suitable for this study. The hope is that the distribution of scholarships will be more efficient and fair, focusing on those in need.